Gender Dynamics in Pandalungan: Women in the Centre of Patriarchy and Egalitarianism - Luthfi, Muhamad; Rofhani, Rofhani (UIN Sunan Kudus, 2025)
This study explores the gender dynamics of Pandalungan women in East Java, who navigate the coexistence of patriarchal culture and egalitarian values. Despite living in a social order dominated by male authority, Pandalungan women show strong independence and decision-making capacity in domestic and public spheres. Their resilience reflects the egalitarian ethos of Madurese culture, where cooperation, mutual respect, and adaptability coexist with traditional hierarchies. Employing a descriptive qualitative method through interviews and literature studies, this research investigates how women position themselves, negotiate authority, and assert agency in family and community life. The findings reveal that while patriarchal norms remain influential, women actively contribute to household economies, education, and community leadership—reshaping conventional gender boundaries. Their participation illustrates that egalitarianism is not merely an imported ideal but a lived cultural practice rooted in local values. Pandalungan women thus become central figures in sustaining family welfare and promoting social balance. The study concludes that the dynamics of patriarchy and egalitarianism in Pandalungan society demonstrate a gradual transformation toward gender equality, where women’s agency evolves through negotiation, collaboration, and moral authority rather than open confrontation.